2014
DOI: 10.3109/01676830.2014.959185
|View full text |Cite
|
Sign up to set email alerts
|

Ga-68-DOTA-TATE PET/CT for Discrimination of Tumors of the Optic Pathway

Abstract: Ga-68-DOTA-TATE PET/CT proved to be a valuable diagnostic tool for the correct classification of equivocal, symptomatic tumors of the anterior optic pathway requiring therapy. PET/CT results influenced therapy decision essentially in all cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 26 publications
4
37
0
2
Order By: Relevance
“…[68 Ga]‐DOTA‐TATE (68‐Ga‐1,4,7,10‐tetraazacyclododecane‐ N , N ’, N ’’, N ’’’‐tetraacetic acid‐d‐Phe(1),Tyr(3)‐octreotate) has proven invaluable for non‐invasive diagnostics of meningioma (Klingenstein et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[68 Ga]‐DOTA‐TATE (68‐Ga‐1,4,7,10‐tetraazacyclododecane‐ N , N ’, N ’’, N ’’’‐tetraacetic acid‐d‐Phe(1),Tyr(3)‐octreotate) has proven invaluable for non‐invasive diagnostics of meningioma (Klingenstein et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Different radiopharmaceutical tracers have given evidence of proving metabolic lineage of orbital metastases (Klingenstein et al 2016). [68 Ga]-DOTA-TATE (68- 4,7,N',N'', acid-d-Phe(1), Tyr(3)-octreotate) has proven invaluable for non-invasive diagnostics of meningioma (Klingenstein et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Unsere Gruppe hat in der Ophthalmologie bereits vom erfolgversprechenden Einsatz der kombinierten FDG-PET/CT (FDG: 18 F-Fluor-Desoxyglukose) bei der Metastasendetektion von Aderhautmelanompatienten [13], der Detektion orbitaler Tumoren mittels verschiedener Tracer [14] und vom Einsatz der 68 Ga-DOTA-TATE-PET/CT ( 68 Ga-1,4,7,10-tetraazacyclododecan-N,N′,N′′, N′′′-tetraessigsäure Phe(1)Tyr(3)-Octreotat) in der Meningeomdiagnostik berichtet [15]. ▶ Abb.…”
Section: Sinnvoller Einsatz Bildgebender Diagnostikunclassified
“…While PET/CT has already been considered as a new method for diagnosing, staging, and restaging patients with orbital lymphoma,14 the advantage in solid orbital tumours is regarded controversial 15. Our study group has reported on (68Ga)-DOTA-TATE PET/CT as a useful tool in imaging orbital meningiomas previously 12. The objective of the current study was to evaluate the performance of the combined PET/CT scanner in patients with primary and secondary solid orbital tumours.…”
Section: Introductionmentioning
confidence: 96%
“…(68Ga)-DOTATATE (68-Ga-1,4,7,10-tetraazacyclododecane-N,N',N'',N'''-tetraacetic acid-d-Phe(1),Tyr(3)-octreotate), a selective somatostatin receptor (SSTR) agonist,12 is applied for the detection of meningioma or neuroendocrine tumours. For imaging of other tumour entities that might metastasise to the orbit, specific radiopharmaceutical tracers such as, for example, (18F)-fluoroethylcholine ((18F)-FEC) or (68Ga)-PSMA (prostate-specific membrane antigen) in prostate cancer are applied regularly in clinical routine among others 13…”
Section: Introductionmentioning
confidence: 99%